Answer:
A. 9x − (−5 + 6x)
D. 9x − (6x − 5)
Explanation:
Select all expressions that at equivalent to the expression 3x + 5.
To get our answer, we have to solve each option
A. 9x − (−5 + 6x)
= 9x + 5 - 6x
= 9x - 6x + 5
= 3x + 5
Option A is correct
B. 9x − (5 − 6x)
= 9x - 5 + 6x
= 9x + 6x - 5
= 15x - 5
Option B is wrong
C. 9x − (6x + 5)
9x - 6x - 5
= 3x - 5
Option C is wrong
D. 9x − (6x − 5)
= 9x - 6x + 5
= 3x + 5
Option D is correct
E. 9x − (−6x + 5)
= 9x + 6x - 5
= 15x - 5
Therefore, Option A and D are the correct options with the right expressions